Population Bottlenecks and Intra-host Evolution During Human-to-Human Transmission of SARS-CoV-2 - Wang, Daxi; Wang, Yanqun; Sun, Wanying; Zhang, Lu; Ji, Jingkai; Zhang, Zhaoyong; Cheng, Xinyi; Li, Yimin; Xiao, Fei; Zhu, Airu; Zhong, Bei; Ruan, Shicong; et al. (Frontiers in Medicine, 2021)
The emergence of the novel human coronavirus, SARS-CoV-2, causes a global COVID-19 (coronavirus disease 2019) pandemic. Here, we have characterized and compared viral populations of SARS-CoV-2 among COVID-19 patients within and across households. Our work showed an active viral replication activity in the human respiratory tract and the co-existence of genetically distinct viruses within the same host. The inter-host comparison among viral populations further revealed a narrow transmission bottleneck between patients from the same households, suggesting a dominated role of stochastic dynamics in both inter-host and intra-host evolutions.